2022
DOI: 10.3390/ijerph191811399
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Malay Version of the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA)

Abstract: The Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) has been translated and adapted globally. This study aimed to examine the psychometric properties of the Malay version of the ERQ-CA. The Malay version of the ERQ-CA underwent forward and back translation twice and was tested in two separate studies, Study 1 and Study 2, with 296 and 359 students aged between 13 and 14 years old, respectively. Cronbach’s alpha values were calculated, and confirmatory factor analysis was conducted. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…The main objective is to have a better grasp of how this scale functions in the Malaysian language and culture. A similar approach from the previous study of translating and validating the questionnaire related to medical assessment into a Malay version has been observed as a valid and reliable tool for assessing educational needs and gathering information among group-based participants in Malaysia 56,[65][66][67][68][69] . To date, none of the studies have been observed using the Malay version of the respiratory symptoms questionnaire in Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…The main objective is to have a better grasp of how this scale functions in the Malaysian language and culture. A similar approach from the previous study of translating and validating the questionnaire related to medical assessment into a Malay version has been observed as a valid and reliable tool for assessing educational needs and gathering information among group-based participants in Malaysia 56,[65][66][67][68][69] . To date, none of the studies have been observed using the Malay version of the respiratory symptoms questionnaire in Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…To increase understanding of emotion dysregulation among adolescents, a tool that is applicable and suitable for the Malaysian population is required. Even though emotion regulation studies have been conducted in Malaysia, they have focused on strategies to regulate emotion [30][31][32][33][34][35]. Nevertheless, an assessment instrument for emotion regulation difficulties has not been validated.…”
Section: Plos Onementioning
confidence: 99%